PENERAPAN NORMA RELIGIUS DALAM MEMBENTUK PERILAKU TELADAN DI KALANGAN SISWA SEKOLAH DASAR - Gaurifa, Timahati (Counseling For All : Jurnal Bimbingan dan Konseling, 2025)
This study aims to explore the application of religious norms in shaping exemplary behavior among students at SD Negeri 076103 Bawoza’ua. The implementation of religious norms, including routine activities such as collective prayers, scripture reading, and religious teachings, is believed to have a positive impact on the development of students' character. This study employs a descriptive qualitative approach with data collection techniques including participatory observation, in-depth interviews, and documentation. The results of the study indicate that the application of religious norms in the school significantly contributes to the formation of students' social and spiritual behavior, including increased discipline, respect, responsibility, and emotional management skills. Furthermore, students who actively participate in religious activities tend to show more empathy towards their peers and demonstrate honesty in exams. Thus, the application of religious norms at SD Negeri 076103 Bawoza’ua strengthens students' moral character and fosters a harmonious and positive school culture